Facile synthesis of magnetic agarose microfibers by directed self-assembly in W/O emulsions. (14th June 2016) - Aldana, Samuel; Vereda, Fernando; Hidalgo-Alvarez, Roque; de Vicente, Juan
Abstract: We propose a new versatile approach for the fabrication of flexible magnetic microfibers having tunable size and mechanical properties. The methodology is based on the magnetic field-driven self-assembly of agarose-loaded kinetically unstable aqueous ferrofluid-in-oil emulsions. Agarose is dissolved at a temperature above its gelling point in an aqueous ferrofluid and the resulting suspension is then emulsified in oil and later exposed to a DC uniaxial magnetic field. Once the fibers have formed, the emulsion is quenched to force the gelification of the agarose, and a second addition of surfactant is carried out to prevent lateral aggregation of the fibers. Resulting fibers have diameters of the order of a few to tens of micrometers. A phase diagram is constructed and the influence of surfactant concentration and residence time under field in the synthesis is discussed. Graphical abstract: Highlights: Magnetic microfibers from self-assembly of unstable ferrofluid-in-oil emulsions. Aspect ratio controlled by the surfactant concentration and field strength. Elasticity of the microfibers controlled by the initial agarose concentration.